Lord Burghley's papers in the British Library in London : produced in their entirety from the Lansdowne Collection, v. 1-122 - Burghley, William Cecil, Baron, 1520-1598; Hawkins, Michael (Politics and administration of Tudor and Stuart England, 1685)
Letters and papers, chiefly relating to government affairs of the Tudor/Stuart period, but ranging from the 13th century to 1685.